Development of system for automatic measurement of transient photocurrent and thermally stimulated current (2017)
This paper presents details of the design and implementation of a system for measuring of thermally stimulated current (TSC) and transient photocurrent (Iph), developed using the Virtual Instrumentation concept. For that we have used National Instrument hardware and the LabView® package as software. The system is controlled by a virtual instrument (VI) which includes facilities to perform measurements of photocurrent keeping the temperature of the sample and the pressure of the chamber of measurement controlled as well as  real time display of the Iph vs t and TSC vs T curves. The system was tested by performing transient photocurrent and TSC measurements on CH3NH3PbI3 thin films that are generally used as absorbent layer of solar cells. This type of characterization is very useful to get information of the  trapping and recombination processes that affect the transport properties of the devices.